PENDAMPINGAN LANSIA DALAM KONTEKS MENJAGA KESEHATAN FISIK DI POSYANDU LANSIA KENTINGAN KULON JEBRES SURAKARTA - Nasri, Nasri; Mei Leni, Ari Sapti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Background : Regular health checks and good exercise can maintain the health of the elderly so that there is no drastic decline. Routine health checks aim to control the health of the elderly on a regular basis so that they can find out what is happening. The obstacles encountered in the partner groups are the lack of awareness of the elderly in maintaining health due to busy work and other activities. Output: increased knowledge of partner groups about health and how to protect them. Method: health education, routine health checks, therapy and exercise to maintain the health of the elderly. Results: after counseling and health assistance before and after the provision of information increased knowledge. Prior to counseling knowledge of the elderly on osteoarthritis disorders by 32% and low back pain by 36%. After being given information, there was an increase of 64% knowledge of osteoarthritis disorders and by 72% knowledge of low back pain disorders. Conclusion: an increase in knowledge in the elderly about osteoarthritis disorders and low back pain.